Nordic children's conceptualizations of healthy eating in relation to school lunch. Issue 2 (6th February 2017) - Berggren, Linda; Talvia, Sanna; Fossgard, Eldbjørg; Björk Arnfjörð, Unnur; Hörnell, Agneta; Ólafsdóttir, Anna Sigríður; Gunnarsdóttir, Ingibjörg; Wergedahl, Hege; Lagström, Hanna; Waling, Maria; Olsson, Cecilia
Abstract : Purpose: Pupils' perspective should be better taken into account when developing nutrition education at school. The purpose of this paper is to explore Nordic children's perspectives on the healthiness of meals in the context of school lunches. Design/methodology/approach: In total, 78 focus group discussions were conducted with 10-11-year-old girls and boys ( n =457) from schools in Finland, Iceland, Norway and Sweden, which were participating in the Nordic school meal project ProMeal during the school year 2013-2014. A flexible discussion guide and stimulus material in the form of 14 photographs displaying different school lunch contexts were used. The discussions were analyzed using thematic analysis. Findings: These Nordic children seem to share the adult-set aim of healthy eating in the school context as a socio-cultural norm. Although healthy eating was constructed as a rational, normative and acceptable way to eat at school, unhealthy eating was emphasized as negotiably acceptable when eaten occasionally and under certain circumstances (e.g. at special occasions). Unhealthy eating also comprised emotionally laden descriptions such as enjoyment and disgust. Practical implications: Children's conceptualizations of healthy eating are connected to nutritional, socio-cultural, emotional and normative dimensions, which should be reflected also when developing nutrition education in school. Originality/value: The need for research exploring children's experiences of, and understandings about, school lunch motivated this unique multicenter study with a large number of participating children. In the focus groups a child-oriented, photo-elicitation method was used.